Vascular Access Complications In Hemodialysis: Comprehensive Review Of Early And Late Manifestations, Risk Factors, And Clinical Management Strategies (The Review of Diabetic Studies, 2024)
End-stage renal disease (ESRD) patients requiring maintenance hemodialysis (MHD) face substantial psychological burden alongside their chronic physical disease, resulting in significant negative impacts on quality of life (QoL). This comprehensive review synthesizes current evidence on the relationships between psychological factors (particularly anxiety and depression), quality of life, and patient education in hemodialysis populations, with emphasis on evidence-based interventions suitable for healthcare technicians and nursing professionals. A systematic search of peer-reviewed literature from 2005 to 2025 identified 15 randomized controlled trials and multiple observational studies examining psychological interventions, patient education strategies, and quality of life outcomes in hemodialysis patients. Findings indicate that depression and anxiety are highly prevalent in MHD patients (prevalence rates ranging from 20-92.4%), with significant negative correlations to all domains of quality of life. Meta-analysis of psychological interventions demonstrated clinically meaningful reductions in depression (mean difference = -4.91, 95% CI -6.56 to -3.26) and anxiety (mean difference = -5.11, 95% CI -6.97 to -3.25) regardless of intervention duration. Educational interventions targeting vascular access care, medical device understanding, and psychoeducational support showed measurable improvements in patient self-care behaviors, self-efficacy, and psychological adjustment. This review emphasizes the critical role of multidisciplinary healthcare teams in implementing screening protocols for mental health disorders, delivering evidence-based psychological interventions, and providing comprehensive patient education to improve treatment adherence, clinical outcomes, and overall quality of life in hemodialysis patients. Healthcare technicians are positioned as frontline providers capable of identifying psychological distress, facilitating access to mental health resources, and reinforcing patient education regarding vascular access maintenance and self-care practices.